2018
DOI: 10.2147/ijn.s152246
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-release of FGF-2 from a hybrid hydrogel of heparin-poloxamer and decellular matrix promotes the neuroprotective effects of proteins after spinal injury

Abstract: Introduction The short lifetime of protein-based therapies has largely limited their therapeutic efficacy in injured nervous post-spinal cord injury (post-SCI). Methods In this study, an affinity-based hydrogel delivery system provided sustained-release of proteins, thereby extending the efficacy of such therapies. The affinity-based hydrogel was constructed using a novel polymer, heparin-poloxamer (HP), as a temperature-sensitive bulk matrix and decellular spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Extracellular matrix is an ideal natural scaffold in tissue regeneration due to their unique architecture, and major compositions are critical to direct the cell attachment and create a favourable bio-environment for cell proliferation, and differentiation. Many other scientists and we have reported that the mixture of decellularized matrix degradation/smash promotes cell proliferation, migration and tissue regeneration [31][32][33]. In our study, the bioactivity of the decellularized matrix was confirmed in the biocompatibility study, and the lixivium of dUECM medium could promote the HUVEC cells proliferation compared to negative control (Figure 4).…”
Section: Discussionsupporting
confidence: 74%
“…Extracellular matrix is an ideal natural scaffold in tissue regeneration due to their unique architecture, and major compositions are critical to direct the cell attachment and create a favourable bio-environment for cell proliferation, and differentiation. Many other scientists and we have reported that the mixture of decellularized matrix degradation/smash promotes cell proliferation, migration and tissue regeneration [31][32][33]. In our study, the bioactivity of the decellularized matrix was confirmed in the biocompatibility study, and the lixivium of dUECM medium could promote the HUVEC cells proliferation compared to negative control (Figure 4).…”
Section: Discussionsupporting
confidence: 74%
“…Yao et al 43 implanted an AFG hydrogel into a rat hemisected SCI model to bridge lesion cavities, which promoted axonal regeneration and locomotor function recovery of rats. Xu et al 44 demonstrated that FGF2loaded dscECM-HP hydrogel can achieve sustained release of FGF2 in vitro and recover both nerve tissue morphology and neuron functions in vivo. Our data showed that injection of HAMC-KAFAK/BDNF hydrogel significantly reduced cavity volume and promoted axonal regeneration and tissue preservation compared to the HAMC or SCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the concentration of rhFGF21 in the collected supernatants was analyzed via HPLC (1260 Infinity LC; Agilent Technologies, Santa Clara, CA, USA). The rhFGF21 release experiment was carried out at 37°C as previously described (13,24) and was maintained until the end of the experiment because rhFGF21-HP was used as a dressing for experimental animals and their body temperature was 37°C. The final concentration of FGF21 at each time point is the sum of the concentration at the specified time point and the concentration at all previous time points.…”
Section: Characterization Of Rhfgf21-hp Hydrogelsmentioning
confidence: 99%
“…Heparin-poloxamer (HP) is a temperature-sensitive hydrogel micelle material that can improve solubility and stability with the proper formulation. Nerve growth factor-loaded HP has been reported to enhance peripheral nerve regeneration (12), and basic fibroblast growth factor (FGF) combined with HP promoted regeneration and functional recovery after spinal cord injury (13). Moreover, 17b-estradiol encapsulated into HP micelles increased endometrial regeneration in intrauterine adhesions (14).…”
mentioning
confidence: 99%